ANALYSIS OF DIRECTLY OBSERVED TREATMENT SHORTCOURSE IMPLEMENTATION AS AN EFFORT TO CONTROL TUBERCULOSIS IN YOGYAKARTA - Liena Sofiana; Muthiah, Tis’a Salma; Putri, Nawwara (The Indonesian Journal of Public Health, 2024)
Introduction: Globally, tuberculosis (TBC) continues to be a factor causing morbidity and death. During the COVID-19 epidemic, case detection has decreased globally; Indonesia is one of the countries that sees this. For many years, the Directly Observed Treatment Shortcourse (DOTS) approach has been used as a TB control program. Based on case studies, the success rate for tuberculosis treatment in Yogyakarta is 86.4%, which does not meet the national target. Aims: To evaluate the Yogyakarta DOTS strategy in reducing TB. Methods: This research uses a qualitative case study design methodology. Six people participated in this research as respondents; two of them were drug swallowing supervisors, and four of them were TBC program participants. Theme analysis was applied to data analysis. Results: Yogyakarta successfully implemented DOTS which consists of five strategies. There are no gubernatorial regulations derived from presidential regulations regarding TB control; however, there was a decision by the governor to accelerate the eradication of TB, which later became a political commitment. Cases were identified through sputum examination using a rapid molecular test. Healthcare institutions have adequate access to medicines, which are monitored by the drug swallowing supervisors. Tuberculosis information system (SITB) is used in monitoring, recording and reporting systems. Conclusion: Implementing the five of Directly Observed Treatment Shortcourse strategies in controlling TBC in Yogyakarta has been done quite well. However, implementation is still hampered by a lack of human resources, computer infrastructure, and connections, all of which impact timely reporting.